LEGAL ANALYSIS OF THE IMPACT OF NARCOTICS USE ON THE HEALTH OF PRISONERS IN WOMEN'S PRISONS TANJUNG GUSTA BASED ON REGULATIONS LEGISLATION - Lasma Sinambela; Ismaidar; Suci Ramadani (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to analyze the legal impact of drug use on the health of inmates at the Tanjung Kusta Women's Detention Center and to examine the handling efforts based on applicable laws and regulations. Drug abuse in detention centers not only violates the law but also has serious impacts on the physical, mental, and social health of inmates, as well as hindering the goals of social development and reintegration. The research method used is empirical legal with a statutory approach, a conceptual approach, and a sociological approach. Primary data were obtained through interviews with prison officers, medical personnel, and inmates, while secondary data were obtained from laws and regulations, legal literature, and official reports. The research results show that legal regulations regarding the prohibition of narcotics use in detention centers are regulated in Law Number 35 of 2009 concerning Narcotics, Law Number 12 of 1995 concerning Corrections (as amended by Law Number 22 of 2022), and Regulation of the Minister of Law and Human Rights Number 6 of 2013 concerning Correctional Institutions/Detention Centers. The resulting impacts include organ damage, the risk of infectious diseases, mental disorders, decreased quality of guidance, and increased recidivism. Handling efforts are carried out through repressive, preventive, and rehabilitative measures, but their implementation is still hampered by limited supervision, facilities, and coordination between institutions. This study concludes that normatively, the existing legal framework is adequate, but its implementation in the field is not optimal. Strengthening the monitoring system, improving rehabilitation facilities, and synergy between relevant agencies are needed to ensure the protection of the health rights of drug-using inmates at the Tanjung Kusta Women's Detention Center.